Fractia o rationalizezi cu 1 + i[tex] \sqrt{3} [/tex] => ( 1 + 2i[tex] \sqrt{3} [/tex] - 3 ) / 4 = ( -2 + 2i[tex] \sqrt{3} [/tex] ) / 4 = ( - 1 + i[tex] \sqrt{3} [/tex] ) / 2;
( 1 - i ) ^943 =[ ( 1 - i )^2]^4721* ( 1 - i ) = ( - 2i )^471 * ( 1 - i ) = -2^471 * i^471 * ( 1 - i ) = - 2^471 * ( - i ) * ( 1 - i ) = 2^471( i + 1 ) ;
Daca intre fractie si paranteza este semnul de inmultire => 2^470 * ( 1 + i ) * ( - 1 + i[tex] \sqrt{3} [/tex] ) = 2^470 * ( - 1 - i + i[tex] \sqrt{3} [/tex] - [tex] \sqrt{3} [/tex] )
Bafta!